Heterogeneous Household Change Among Children - Kristin L. Perkins (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2024)
Family instability has negative consequences, on average, for child and adolescent behavior, cognitive scores, and educational attainment. Beyond changes involving parents, many children experience household changes involving extended family and nonrelatives. These children are less likely to graduate from high school and complete some college than those who experience no such changes. Research finds small or insignificant negative consequences of these changes among Black children. I estimate heterogeneous effects of household changes involving parents, extended family, and nonrelatives on educational attainment among Black children based on the likelihood of such changes. Black children least likely to experience changes experience stronger negative effects on educational attainment than those moderately and most likely to do so. Black children who are least and moderately likely may be more negatively affected in terms of some college completion relative to Black children who are most likely to experience this type of household change.